The Effect of Providing Tepid Sponge Education on Mother's Knowledge In Reducing Fever In Children - Gusti Barlia Gusti; Wiradianto Putro (Program Studi Keperawatan Universitas Muhammadiyah Tasikmalaya, 2023)
Tepid sponge compresses is a non-pharmacological therapy to reduce fever for children. Mother's knowledge about the tepid sponge compress is needed so education needs to be given. The aim is to develop knowledge of mothers in reducing fever in children by using the Tepid Sponge Compression Technique. The type of this research is. Quasi Experiment Design used is Pretest-Posttest Control Group Design. The target population in this study were mothers with children of 5 – 10 years in the working area of the Seelakau Public Health Center. With an average value that has increased as much as 44.9932 in the intervention group and in the control group also increased by 8.5107. Based on the results of Wilcoxon statistical tests that show Asymp. Sig. (2-Tailed) is 0.000, meaning that there is a difference between the groups using video and those not using video. Counseling will work well when using the right methods and tools that are of interest to the respondents. The use of video in this study functions well as an extension tool for the Tepid Sponge Compress.